PERAN UNICEF DALAM PROSES DISARMAMENT, DEMOBILIZATION, REINTEGRATION PRAJURIT ANAK PASCA PERANG SIPIL DI CHAD - Nadila, Kania Farisa; Windiani, Reni; Paramasatya, Satwika (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
This research is inspired by the civil war that took place in Chad in 2005 until 2010. This war caused humanitarian impacts, one of which is the recruitment of child soldiers. The child soldiers were recruited by both the government and the opposition armed forces. The recruitment of child soldiers is listed as a war crime as explained in the Convention on the Rights of the Child, which clearly explains that children under 18 years of age are not allowed to be involved directly in wars as soldiers or combatants. To mitigate and prevent this issue from happening again, the children who are already in the armed forces have to be released through Disarmament Demobilization Reintegration (DDR) process. Unfortunately, Chadian government was unable to handle this by itself since the conflict was still ongoing in that country, and needed help from an organization or institution to go through the DDR process. To explain this situation, neoliberal institutionalism is best suited since its main paradigm is that a country can solve its problem by seeking help from a certain institution, be it old or new. UNICEF, as the only UN body that focuses on children, helped the government of Chad with the DDR process by making an agreement upon this issue. Through this process, UNICEF was able to help advocating the release of more than 1000 child soldiers, help them through the transition and adaptation phase, provide them with accessible healthcare as well as education, and identify the children before they were reintegrated with their families.